Proses Produksi Feronikel dari Bijih Nikel Laterit dengan Metode Rotary Kiln – Electric Furnace (RKEF) - Sudaryanto Sudaryanto; Untung Sukamto; Ibnu Cahyo Nugroho (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
Indonesia is one of the leading producers of nickel. The process of producing nickel from laterite ore is mainly used to make ferronickel, nickel matte, or nickel metal. Laterite nickel ore with a Ni content greater than 1.8% can be processed through pyrometallurgical methods. The production of ferronickel using the Rotary Kiln-Electric Furnace method involves a series of steps, including the transportation of raw materials, drying of samples, moisture content testing, sample testing, smelting, pouring, and metal testing. The object of this study is laterite nickel from the Bahodopi and Pomalaa sites of PT Vale Indonesia Tbk. The object has been divided into four samples, namely Bahodopi Low Limit, Bahodopi Upper Limit, Pomalaa Low Limit, and Pomalaa Upper Limit, with varying levels of nickel content. The aim of this research is to produce ferronickel with a high nickel grade. The grade and recovery of nickel from the smelting of Bahodopi Low Limit, Bahodopi Upper Limit, Pomalaa Low Limit, and Pomalaa Upper Limit samples are as follows grade Ni 7.98%; 12.75%; 8.94%; 10.85% and recovery Ni 37.46%; 90.52%; 50.43%; 86.85%. The low grade and recovery in the Bahodopi Low Limit sample can be attributed to the initial nickel melted being much lower than the other samples and the appearance of eustantite, clinoesntantite ((Fe,Ni,Mg)2Si2O6), and forsterite (Mg1.7NiO.3O4Si) phases in the slag which can trap nickel and iron so that they remain in the slag.